2001
DOI: 10.1136/gut.48.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of oesophageal acid exposure with Barrett's oesophagus length

Abstract: Background-Gastro-oesophageal reflux disease (GORD) plays a major role in the development of Barrett's oesophagus. However, it has yet to be elucidated what factors determine the length of Barrett's mucosa in each individual patient. Aims-To determine if there is a correlation between oesophageal acid exposure and the length of Barrett's mucosa. We also compared the extent of oesophageal acid exposure between patients with short segment (SSBE) and long segment (LSBE) Barrett's oesophagus. Methods-Twenty seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
80
1
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 23 publications
8
80
1
7
Order By: Relevance
“…5 For example, it was reported that the amount and duration of oesophageal acid exposure correlate well with the length of BE. [6][7] Similarly, the prevalence and size of hiatus hernia is higher among patients with longer segments of BE when compared to subjects with short segment BE or no BE. 5,8 Barrett's oesophagus is an acquired condition and is thought to develop in adulthood as a result of faulty healing of oesophageal mucosa damaged by gastrooesphageal reflux.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…5 For example, it was reported that the amount and duration of oesophageal acid exposure correlate well with the length of BE. [6][7] Similarly, the prevalence and size of hiatus hernia is higher among patients with longer segments of BE when compared to subjects with short segment BE or no BE. 5,8 Barrett's oesophagus is an acquired condition and is thought to develop in adulthood as a result of faulty healing of oesophageal mucosa damaged by gastrooesphageal reflux.…”
Section: Introductionmentioning
confidence: 97%
“…[5][6][7][8][9][10][11][12][13][14][15][16]. Of all patients, 139 (41%) had prior use of histamine-2 receptor antagonists, or proton-pump inhibitors (41 used both), and 201 (59%) used neither prior to the diagnosis of Barrett's oesophagus.…”
mentioning
confidence: 99%
“…The reason for intestinal metaplasia appears to be chronic reflux of gastric (generally acidic) contents into the lower esophagus (Fass et al, 2001). The process leading to intestinal metaplasia may be associated with chronic inflammation (Atherfold and Jankowski, 2006).…”
Section: The Upper Gastrointestinal Tractmentioning
confidence: 99%
“…The development of a Barrett's esophagus is the result of a longstanding reflux of acid and bile. 11,12 The etiopathogenesis of cardiac adenocarcinomas is less clear. Carditis and intestinal metaplasia are proposed as precursor lesions for this cancer.…”
mentioning
confidence: 99%